Enhancing organizational performance through performance management systems and managerial accountability: The role of managerial competence - Thamrin, Dara Alifa Fajriati; Pratolo, Suryo (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study aims to explore whether performance management systems (PMS) and managerial accountability (MA) affect organizational performance. It also considers managerial competence (MC) as a key factor in private higher education institutions (PHEIs) in Indonesia.Design/Methodology/Approach: The survey design employed a quantitative approach, utilizing questionnaires to collect data from 270 higher-ups in PHEIs in Indonesia. The relationships between the factors were determined using structural equation modeling (SEM) analysis to test direct and indirect effects.Research findings: The results unveiled that MC had a substantial influence on PMS, yet it did not directly affect MA or organizational performance. PMS enhanced both MA and organizational performance, and MA further improved performance. A serial mediation demonstrated that PMS and MA worked together to affect organizational performance, indicating that competence improved performance indirectly through better PMS and stronger accountability.Theoretical contribution/Originality: The current research proposes an extensive integration of theories, utilizing concepts from the resource-based view, goal setting, stewardship, resource orchestration, and equity theories, to examine how management capability influences organizational performance through PMS and MA.Practitioner/Policy implication: The study only considered PHEIs within Indonesia. Future studies could broaden their focus to include public universities or employ qualitative techniques to explore the causal processes underlying the observed patterns more thoroughly.Research limitation/Implication: The study only covers Indonesian companies; thus, future research should expand or add qualitative perspectives to acquire deeper insights.